Psychopersonal characteristics of women with varying degrees of menopausal disorders - N. S. Lutsenko; O. D. Mazur; O. S. Shapoval; L. I. Zvarich; N. F. Efimenko (Сучасні медичні технології)
The perimenopausal period is the age of the highest spiritual and intellectual development of a woman; therefore, neurovegetative and psycho-emotional disorders of this period acquire a pecial medical and social value and require an interdisciplinary approach.